2005
DOI: 10.1098/rsif.2005.0082
|View full text |Cite
|
Sign up to set email alerts
|

Diving behaviour of whale sharks in relation to a predictable food pulse

Abstract: We present diving data for four whale sharks in relation to a predictable food pulse (reef fish spawn) and an analysis of the longest continuous fine-resolution diving record for a planktivorous shark. Fine-resolution pressure data from a recovered pop-up archival satellite tag deployed for 206 days on a whale shark were analysed using the fast Fourier Transform method for frequency domain analysis of time-series. The results demonstrated that a free-ranging whale shark displays ultradian, diel and circa-lunar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
4
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 21 publications
10
90
4
4
Order By: Relevance
“…Godo & Michalsen 2000, Righton et al 2001). An exception is the recent use of spectral analysis for distinguishing between normal and reverse diel vertical migration in planktivorous sharks (Graham et al 2006). Various methods for classifying dives for airbreathing vertebrates have been used, often involving multi-variant techniques that summarise the duration, depth and shape of dive profiles (Schreer et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Godo & Michalsen 2000, Righton et al 2001). An exception is the recent use of spectral analysis for distinguishing between normal and reverse diel vertical migration in planktivorous sharks (Graham et al 2006). Various methods for classifying dives for airbreathing vertebrates have been used, often involving multi-variant techniques that summarise the duration, depth and shape of dive profiles (Schreer et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, sharks often performed deep, fast dives below 300 m in offshore locations. Graham et al (2006) found that deep diving in whale sharks was non-randomly distributed, being more regular when a predictable food source was apparently no longer available. A similar pattern has been observed in a leatherback turtle, with more deep dives being performed after the turtle left a suitable prey field (Doyle et al 2008).…”
Section: Vertical Movements and Behaviourmentioning
confidence: 99%
“…Whale sharks are commonly observed at the ocean surface; however, they have recently been tracked to dive to bathypelagic (>1000 m) depths (Graham et al 2006, Brunnschweiler & Sims 2011. While whale sharks spend a lot of their time in the epipelagic zone, these deep dives are intriguing and have been hypothesised to be foraging related (Brunnschweiler & Sims 2011).…”
Section: Feeding At Depthmentioning
confidence: 99%